INFLUENCE OF SALT STRESS ON GROWTH, LEAF PIGMENTATION, IONIC DISTRIBUTION AND METABOLITES ACCUMULATION OF TALINUM TRIANGULARE (JACQ.) WILLD. LEAFY VEGETABLES AS AFFECTED BY DIFFERENT CASSAVA PEEL LEVELS - HAND, Mathias Julien; Ervé NOUCK, Alphonse; Maina NASSOUROU, Antoine; Fanta ABIB, Chimène; Brice TONFACK, Libert; Désiré TAFFOUO, Victor; YOUMBI, Emmanuel (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
Talinum triangulare Jacq. (Water leaf) is a leafy vegetable eaten in most countries in Africa in preparation of soups to enrich the starchy main dishes due to its tastes, medicinal uses such as antiinflammation, anti-fungal, anti-bacterial properties. Impact of four levels of cassava peel (0, 9, 12 and 15 t ha-1) in water leaf in terms of leaf pigment, nutrients, matabolites, antioxidant compounds, minerals, growth and yield under salt stress (0, 50, 100 and 200 mM NaCl) were investigated. Results show that salinity decreased growth parameters, total photosynthetic pigments, ascorbic acid and yield components accompanied by increases in sodium content, carbohydrate, soluble proteins, tannins total phenolic content and flavonoid in the leaf of water leaf. On the other hand, all applied treatments cassava peel caused significant increases in most parameters under investigation as growth parameters, minerals content, all components of photosynthetic pigments, and leaf yield, metabolites. It is obvious that cassava peel treatment at 15 t ha-1 was the most pronounced treatment either under non saline conditions or under salt stress conditions. Increased osmolyte and metabolite accumulation, and redox components in CP supplemented plants regulated the NaCl tolerance by further strengthening the antioxidant mechanisms. The increasing CP supplementation regulates salt tolerance in T. triangulare through modulations in the metabolism of antioxidants, osmolytes and metabolites.